A modified CTAB method for extracting high-quality genomic DNA from aquatic plants - Valiya Thodiyil, Jaseela; Edathumthazhe Kuni , Sinisha; Nediyaparambu Sukumaran , Pradeep (Plant Science Today, 2024)
This study introduces a streamlined approach for extractinghigh-quality DNA fromaquatic plants using CTAB, catering to molecular studies. Seven aquatic plant species(Hygrophilaauriculata, Limnophilarepens, Crinum malabaricum, Lagenandraovata, Ludwigiaperuviana, Eichhorniacrassipes, and Ipomoea aquatica) spanning six orderswere subjected toDNA extraction. The method combinesmechanical lysis and chemical treatments to effectively disrupt cells, coupled with RNase treatment and phenol extraction to mitigate RNA and protein contamination. The optimizedCTAB protocol facilitatesthe extraction of high-quality genomic DNA, suitable for amplifying plant barcode genes such as ITS and rbcL, as well asmarkerslike RAPD and ISSR, thereby enhancing the efficiency and reliability of genomic studies in aquatic plants.